The Latín American psychology in the XX century: An analysis of its characteristics - Alarcón, Reynaldo (1999)
In arder ro identifY rhe most important characrerisrics rhat describe rhe Latín American Psychology ar rhe end of rhe century, six main issues áre discussed: rhe scientific orienration, the dependency characteristic, the lack of an original arproach, the social meaning, the politic permeabiliry, rhe emphasis on applied research, and the interest in the person as the central object of study. The fact that these observations are based on the more active nations in rhe generation of psychological knowledge could be a limitation in rhe generalization of rhe findings.